1989
DOI: 10.1111/j.1651-2227.1989.tb17947.x
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism and Insulin Secretion in Infants with Symptomatic Ventricular Septal Defect

Abstract: Nineteen infants with symptomatic ventricular septal defect (VSD) were examined on, altogether, 26 occasions, when each was given an intravenous glucose tolerance test (IVGTT); concentrations of insulin- and C-peptide in plasma were determined. Comparisons were made with 14 healthy infants of the same age. The VSD infants were growth retarded with lower weight/age and length/age ratios. Glucose tolerance as indicated by glucose fasting levels and response to intravenous glucose tolerance test, including glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
0
4
1
Order By: Relevance
“…The insulin determinations in plasma in the CHD group did not show the lower levels as we previously reported for infants with VSD (7). The fasting and maximum levels and circulating stress hormones which leads to an increased density of a 2 receptors and the downregulation of padrenoreceptors.…”
Section: Discussioncontrasting
confidence: 49%
See 3 more Smart Citations
“…The insulin determinations in plasma in the CHD group did not show the lower levels as we previously reported for infants with VSD (7). The fasting and maximum levels and circulating stress hormones which leads to an increased density of a 2 receptors and the downregulation of padrenoreceptors.…”
Section: Discussioncontrasting
confidence: 49%
“…The reason for the probable increased insulin secretion is unclear. To our knowledge, there are no reports of C-peptide in children with CHD, apart from our recent study (7), and this also applies to healthy infants within this age group.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Lundell et al found increased insulin secretion in combination with low plasma insulin after an intravenous glucose tolerance test in CHD patients with ventricular septal defects compared with healthy controls. This suggested that increased peripheral binding or extraction of insulin is present in infants with CHD after carbohydrate loading (22). Furthermore, upon intravenous lipid loading, disturbances in plasma free-fatty acid levels have been described in infants with CHD (patients with a ventricular septum defect or transposition of the great arteries) (23).…”
Section: Discussionmentioning
confidence: 99%